2006
DOI: 10.1130/g22985a.1
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary textures formed by aqueous processes, Erebus crater, Meridiani Planum, Mars

Abstract: New observations at Erebus crater (Olympia outcrop) by the Mars Exploration Rover Opportunity between sols 671 and 735 (a sol is a martian day) indicate that a diverse suite of primary and penecontemporaneous sedimentary structures is preserved in sulfate-rich bedrock. Centimeter-scale trough (festoon) cross-lamination is abundant, and is betterexpressed and thicker than previously described examples. Postdepositional shrinkage cracks in the same outcrop are interpreted to have formed in response to desiccatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 10 publications
2
97
0
Order By: Relevance
“…6). Several examples of small-scale trough crosslamination and shrinkage cracks at Erebus crater were previously described by Squyres et al (2006) and Grotzinger et al (2006). Some facies could be correlated between a few adjacent outcrop blocks, but there were no facies patterns that could be correlated across the Olympia outcrop due to their displacement and rotation.…”
Section: Olympia Outcrop Stratigraphymentioning
confidence: 95%
See 4 more Smart Citations
“…6). Several examples of small-scale trough crosslamination and shrinkage cracks at Erebus crater were previously described by Squyres et al (2006) and Grotzinger et al (2006). Some facies could be correlated between a few adjacent outcrop blocks, but there were no facies patterns that could be correlated across the Olympia outcrop due to their displacement and rotation.…”
Section: Olympia Outcrop Stratigraphymentioning
confidence: 95%
“…The sulfate-rich bedrock exposed along the walls at Eagle and Endurance craters has been interpreted by the MER team to have been deposited in an eolian dune-interdune environment Grotzinger et al 2005;Grotzinger et al 2006). This interpretation of the outcrops has been challenged by McCollom and Hynek (2005) and Knauth et al (2005), who suggested that volcanic or impact-related sedimentation was responsible for the deposition of the Meridiani bedrock.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations